2010
DOI: 10.1007/s11104-010-0643-4
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere disturbance influences fungal colonization and community development on dead fine roots

Abstract: Little is known about the community dynamics of fungi on decomposing fine roots, despite the importance of fine roots as a source of carbon to detrital systems in forests. We examined fungal communities on dead roots in a sugar-maple dominated northern hardwood forest to test the hypothesis that community development is sensitive to rhizosphere disruption. We generated cohorts of dead fine roots in root windows and disturbed the rhizosphere microbial community in half of the windows by moving roots into sieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…However, its thin hyphae, which measure 1–2 μm in diameter, may persist better in an undisturbed habitat. Umbelopsis is a later decay fungus which dominates in an undisturbed community (Fisk, Fahey, Sobieraj, Staniec, & Crist, ). The presence of Wilcoxina mikolae only in undisturbed soil was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…However, its thin hyphae, which measure 1–2 μm in diameter, may persist better in an undisturbed habitat. Umbelopsis is a later decay fungus which dominates in an undisturbed community (Fisk, Fahey, Sobieraj, Staniec, & Crist, ). The presence of Wilcoxina mikolae only in undisturbed soil was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches limit rhizosphere disturbance and allow for functional comparisons among roots within the fine root branching system in situ (Dornbush et al 2002;Fisk et al 2011). Both the intact core and root window approaches maintain connectivity among belowground branching systems and do not require preliminary processing of root material (Dornbush et al 2002).…”
Section: Methodological Considerations For Future Studiesmentioning
confidence: 99%
“…For first order roots to maintain situational context, they must decompose in the presence of intact rhizosphere soil, colonized by pre-mortem fungi (Li et al 2015). Fisk et al (2011) disrupted the rhizosphere of roots decaying under root windows inset into the soil in an Eastern hardwood forest and found that the dominant fungal taxa changed due to the disturbance; rhizosphere species were replaced by bulk soil fungal species. Dornbush et al (2002) decomposed recently senesced fine roots of silver maple using both litterbags and an intact core technique where roots are left to decompose within an intact soil core to limit rhizosphere disturbance.…”
Section: Maintaining Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…We sampled after plant senescence in October 2013, a period when tree C allocation belowground is likely to be at annual minima (Abramoff and Finzi, 2016), potentially affecting the root-associated fungal communities that we observed. For example, sugar maple associates primarily with arbuscular mycorrhizal fungi and AMF root-colonization, abundance, and biomass are likely to be highest during periods of higher plant C allocation belowground in mid-summer (Mandyam and Jumpponen, 2008; Soudzilovskaia et al, 2015) whereas saprotroph abundance would be expected to increase following root senescence (Fisk et al, 2011).…”
Section: Discussionmentioning
confidence: 99%